Digital Taxation and Sustainable Development: Post-Pandemic Evidence - Nurhayati; Meta Nursita; Lokita Rizky Megawati (School of Business, IPB University (SB-IPB), 2026)
Background: The COVID-19 pandemic has significantly reshaped the global economic and business landscape by accelerating digital transformation. This shift has intensified the complexity of international taxation systems, particularly in addressing cross-border digital activities, while simultaneously highlighting the growing importance of aligning fiscal policies with sustainable development objectives.Purpose: This study aims to examine how digital transformation in the post-pandemic era has reshaped international taxation dynamics, particularly in terms of its implications for government revenue, business behavior, and sustainable development outcomes.Design/methodology/approach: This research employs a mixed-method approach, combining qualitative and quantitative analyses through a comparative framework of international taxation systems. The study relies on secondary data obtained from government reports, tax authorities, international organizations, and peer-reviewed academic literature.Findings: The findings indicate that digital transformation has significantly increased the complexity of tax collection, particularly in relation to cross-border digital transactions and tax avoidance practices. At the same time, digital taxation policies have measurable effects on government revenue and firm behavior. Furthermore, taxation instruments such as digital taxes and carbon taxes play a crucial role in supporting sustainable development by financing public services, reducing environmental externalities, and addressing income inequality.Conclusion: The international taxation system must adapt to the challenges of digitalization by strengthening regulatory frameworks, enhancing transparency, and fostering international cooperation. Coordinated global efforts are essential to reduce tax avoidance, ensure fair tax allocation, and support sustainable economic development.Originality/value: This study contributes to literature by integrating digital taxation, pandemic-driven economic transformation, and sustainable development into a unified analytical framework. It offers policy-relevant insights by linking international tax reforms with sustainability objectives in the digital economy. Keywords:digital economy, digital taxation, international taxation, sustainable development, tax avoidance